Pedagogical Content Knowledge (PCK) of Prospective Science Teachers in ASEAN to Realize Sustainable Development Action - Riska Septia Wahyuningtyas; Manogari Sianturi; Elferida Sormin; Candra Ditasona; Santri Chintia Purba; Stevi Natalia; Merle L. Junsay; Rene Estomo; Hotmaulina Sihotang (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2025)
Prospective science teachers must master pedagogical knowledge (PK) and content knowledge (CK), commonly referred to as Pedagogical Content Knowledge (PCK), before entering the teaching profession. PCK is essential professional knowledge that supports effective science teaching. This study aims to analyze the PCK readiness of prospective science teachers in Indonesia and the Philippines, with a focus on the CK and PK competencies required for teaching in the ASEAN context. The study employed a mixed-methods approach. Survey data were collected from 110 prospective science teachers undertaking field teaching practice in schools in Indonesia and the Philippines. In addition, in-depth interviews were conducted with 12 participants, consisting of six prospective teachers from each country. The data focused on participants’ understanding and preparation related to pedagogical skills and science subject matter. The results indicate that the overall PCK level of prospective science teachers falls within the “moderately ready” category. However, the proportion of participants classified as “ready” remains relatively low, ranging from 44.9% to 58.5%. These findings suggest a need for strengthening both PK and CK among prospective science teachers. Enhancing PK can be achieved through additional pedagogical education and targeted training programs to improve teaching skills. Meanwhile, improving CK can be supported by providing more specialized science content courses aligned with school curricula prior to teaching practice. PCK readiness plays a crucial role in supporting sustainable development. Beyond integrating pedagogy and content, PCK enables prospective teachers to effectively convey scientific concepts related to sustainability issues: climate change, natural resource conservation, environmentally friendly technologies.